Melanoma, Melanin, and Melanogenesis: The Yin and Yang Relationship - Slominski, Radomir M.; Sarna, Tadeusz; Płonka, Przemysław M.; Raman, Chander; Brożyna, Anna A.; Slominski, Andrzej T. (Frontiers in Oncology, 2022)
Melanin pigment plays a critical role in the protection against the harmful effects of ultraviolet radiation and other environmental stressors. It is produced by the enzymatic transformation of L-tyrosine to dopaquinone and subsequent chemical and biochemical reactions resulting in the formation of various DHICA and DHI oligomers - main constituents of eumelanin, and benzothiazine and benzothiazole units of pheomelanin. The biosynthesis of melanin is regulated by sun exposure as well as by many hormonal factors at the tissue, cellular and subcellular levels. While the presence of melanin protects against the development of skin cancers including cutaneous melanoma, its presence may be necessary for the malignant transformation of melanocytes. This shows a complex role of melanogenesis in melanoma development defined by chemical properties of melanin and the nature of generating pathways such as eu- and pheomelanogenesis. While eumelanin is believed to provide radioprotection and photoprotection by acting as an efficient antioxidant and sunscreen, pheomelanin, being less photostable, can generate mutagenic environment after exposure to the short-wavelength UVR. Melanogenesis by itself as well as its highly reactive intermediates show cytotoxic, genotoxic, and mutagenic activities, and it can stimulate glycolysis and HIF-1α activation, which combined with their immunosuppressive effects, can lead to melanoma progression and resistance to immunotherapy. On the other hand, melanogenesis related proteins can be a target for immunotherapy. Interestingly, clinicopathological analyses on advanced melanomas have shown a negative correlation between tumor pigmentation and diseases outcome as defined by overall survival and disease-free time. This indicates a “Yin and Yang” role for melanin and active melanogenesis in melanoma development, progression, and therapy. Furthermore, based on the clinical, experimental data and diverse effects of melanogenesis we propose that inhibition of melanogenesis in advanced melanotic melanoma represents a realistic adjuvant strategy to enhance immuno-, radio- and chemotherapy.